2012
DOI: 10.4236/ojbiphy.2012.24016
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Exposure of Leukemia Blood Samples and Its Impacts on the Density of RBC, WBC, and PLT: <i>In Vitro</i>

Abstract: Complete blood counts were analyzed for 12 samples (six males & six females: Ages 15 -40 years) of leukemia blood Samples for different dose rate and time of exposure using a Radium-226 source. Thus, an optimum time of exposure and exposure dose rate has improved for leukemia blood samples. Blood samples fractionated and placed in plastic wills, and melodic Coulter used to analysis exposed leukemia blood samples before and after exposure. Exposure technique involving CR-39 nuclear track detector and radiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Furthermore, the result of the present study can be explained by the fact that the workers in the catheterization lab were not previously exposed to any substance that affected the hematological parameters as compared with the control. The present results show a behavior that is consistent with the results of Ismail et al [ 17 ] and Hamzah et al [ 18 ]. Moreover, these results are not consistent with reported investigations [ 9 ] in Iran that showed a linear relationship between exposure doses and blood parameters of staff working in catheterization laboratories who were exposed to continuous radiation.…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, the result of the present study can be explained by the fact that the workers in the catheterization lab were not previously exposed to any substance that affected the hematological parameters as compared with the control. The present results show a behavior that is consistent with the results of Ismail et al [ 17 ] and Hamzah et al [ 18 ]. Moreover, these results are not consistent with reported investigations [ 9 ] in Iran that showed a linear relationship between exposure doses and blood parameters of staff working in catheterization laboratories who were exposed to continuous radiation.…”
Section: Discussionsupporting
confidence: 94%
“…Several previous studies related to the effect of radiation doses on RBC levels have been carried out. Ismail et al (2012) found that changes of the density of WBCs, PLTs, and RBCs were variable due to the exposure dose rate. The optimum exposed dose rate to make more adverse effects on the leukemia blood samples began at the radiation dose rate of 43.25 ± 1.206 μSv/h for males and females.…”
Section: Rbcs Dosementioning
confidence: 99%
“…The optimum exposed dose rate to make more adverse effects on the leukemia blood samples began at the radiation dose rate of 43.25 ± 1.206 μSv/h for males and females. Surely, it needs to be considered from the level of DNA damage, especially double-strand break [25]. Furthermore, several types of single nucleotide polymorphisms indicate an association with the level of DNA damage on cancer patients and play a role in the risk of obesity in Javanese ethnicity of Indonesia [26,27].…”
Section: Rbcs Dosementioning
confidence: 99%
“…worms and parasites. Granulocytes are dividing into monocytes (macrophages and dendrites) and lymphocytes (B-cells and T-cells) [2][3]. Their functions are to stimulate osteoclasts cells, antibodies and protein production, producing cytokines which help to direct to respond to calls, etc.…”
Section: Introductionmentioning
confidence: 99%